MODEL WORK-LIFE BALANCE DALAM PENINGKATAN EMPLOYEE ENGAGEMENT PADA PEREMPUAN BEKERJA YANG MENJALANI PERAN GANDA (PSYCHOPEDIA : Jurnal Psikologi Universitas Buana Perjuangan Karawang, 2022)
Women who have multiple roles hope to live a balanced life. On the one hand, as an employee, she tries to be engaged in her work to a maximum performance. On the other hand, personal matters, household domestic tasks can be completed satisfactorily to make them happy. One of the efforts that can be made by women who have multiple roles to remain engaged in their work is to balance their personal affairs with their work or work-life balance. The purpose of this study was to determine the effect of work-family balance on the work engagement of working women who have multiple roles. This research method is quantitative-causal comparative with a purposive sampling technique, involving 201 working and married mothers in Indonesia. The work-life balance measurement tool refers to the theory of Greenhaus et.al (2002) with 21 valid items (range (r) ≥ 0.3) and reliability (α) = 0.905. The work engagement scale uses the Utrecht Employee Engagement Scale (UWES) from Schaufeli and Bakker (UWES) adapted from Titien (2016) with 28 valid items and reliability (α) = 0.922. The results of this study indicate that there is an effect of work-life balance on work engagement in working women who have multiple roles with a significant value (p) of 0.000 (p